-8-6=7x-2-6x

Simple and best practice solution for -8-6=7x-2-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-6=7x-2-6x equation:


Simplifying
-8 + -6 = 7x + -2 + -6x

Combine like terms: -8 + -6 = -14
-14 = 7x + -2 + -6x

Reorder the terms:
-14 = -2 + 7x + -6x

Combine like terms: 7x + -6x = 1x
-14 = -2 + 1x

Solving
-14 = -2 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-14 + -1x = -2 + 1x + -1x

Combine like terms: 1x + -1x = 0
-14 + -1x = -2 + 0
-14 + -1x = -2

Add '14' to each side of the equation.
-14 + 14 + -1x = -2 + 14

Combine like terms: -14 + 14 = 0
0 + -1x = -2 + 14
-1x = -2 + 14

Combine like terms: -2 + 14 = 12
-1x = 12

Divide each side by '-1'.
x = -12

Simplifying
x = -12

See similar equations:

| 6x-(8X+9)=2x-17 | | 9x+16y=-2 | | Sqrtx^2+7=x+1 | | 5*(x+8)=110 | | 26-u=234 | | 41.73/4.00x | | -4(3y+2x)= | | 70=164-v | | 6.78=2X/0.4-X | | 11x-67=77+2x | | x+x+1+x+2+x+3=-74 | | 3=23-5m | | -3(9+-2y+2.5z)+5y+2z=-27 | | 6(ax+3b)= | | 3+3x-1=9x+4-7x | | 14=4g-2 | | -4+(-24)=12 | | x-(3+x)+6=x-2[x-(3x+4)] | | (x-2)^1/2=(28-2x)^1/4 | | 8(3k-7)=64 | | 15x-6=360 | | x+x-1=2x+3 | | x=2y^2-20y+32 | | 9/2.65 | | -9x+15=3x-18 | | 2x^2+56x-36=0 | | k+x=2k-5 | | 4x+7-4x=x-2-4x | | 11y-5x=18 | | -66-x=-8x+95 | | 177w+19=500 | | 3(x+6)=2(x+15) |

Equations solver categories